Heritability of musculoskeletal pain and pain sensitivity phenotypes: 2 generations of the Raine Study. Issue 4 (25th April 2022) - Waller, Rob; Melton, Philllip E.; Kendell, Michelle; Hellings, Sophie; Hole, Erlend; Slevin, Alison; Soares, Jian; Jacques, Angela; Straker, Leon; Beales, Darren
Abstract : This intergenerational population-based investigation reports significant heritability of both musculoskeletal pain and pressure pain sensitivity but not cold pain sensitivity, using robust statistical analysis. Abstract: There is a need to better understand biological factors that increase the risk of persistent musculoskeletal (MSK) pain and heightened pain sensitivity. Knowing the heritability (how genes account for differences in people's traits) can enhance the understanding of genetic vs environmental influences of pain and pain sensitivity. However, there are gaps in current knowledge, including the need for intergenerational studies to broaden our understanding of the genetic basis of pain. Data from Gen1 and Gen2 of the Raine Study were used to investigate the heritability of MSK pain and pressure and cold pain sensitivity. Participants included parents (Gen1, n = 1092) and their offspring (Gen2, n = 688) who underwent a battery of testing and questionnaires including pressure and cold pain threshold testing and assessments of physical activity, sleep, MSK pain, mental health, and adiposity. Heritability estimates were derived using the Sequential Oligogenic Linkage Analysis Routines software. Heritability estimates for MSK pain and pressure pain sensitivity were significant, accounting for between 0.190 and 0.289 of the variation in the phenotype. By contrast, heritability of cold pain sensitivity was not significant. This is the largest intergenerational study to date to comprehensively investigate the heritability of both MSK pain and pain sensitivity, using robust statistical analysis. This study provides support for the heritability of MSK pain and pain sensitivity to pressure, suggesting the need for further convergence of genetic and environmental factors in models for the development or maintenance of these pain disorders.